Locative Media App : mycapsule : a Study in Locative Media, Interface Design, and App Development - Hestekin, Derek; Thorsell, Stephen (My University, 2013)
Due to the increased sophistication of mobile technology and increased popularity of locative media, the goal was to create an interesting mobile app that was technologically functional with a user-friendly interface design. Through informal interviews with mobile app users and researching existing technologies and interface designs used in locative media apps, the group decided to create a location-aware app that served as a virtual time capsule, entitled myCAPSULE. The purpose of this study was to explore how individuals experience locative media through technology in regard to physical space, virtual space, and location-aware surveillance.
Color poster with text and images.
Keywords: myCAPSULE (Application software); Locative media; Posters